Author Correction: The identification of carbon dioxide mediated protein post-translational modifications - Victoria L. Linthwaite; Joanna M. Janus; Adrian P. Brown; David Wong-Pascua; AnnMarie C. O’Donoghue; Andrew Porter; Achim Treumann; David R. W. Hodgson; Martin J. Cann (Nature Communications, 2018)
The original version of this Article omitted the following from the Acknowledgements: ‘This work was support by EPSRC grant EP/K504336/1 and Leverhulme Trust grant RPG-2016-017.’ This has been corrected in both the PDF and HTML versions of the Article.